Influence of Confucianism on development of modern society of People’s Republic of China - Тургенбaй A.A., A.; Оразбекова, Г. Р.; Қалибай, Р. (Journal of Oriental Studies, 2017)
In this article discusses the cause of economic and social economic development of China in the XXI century, it is regarded as Confucianism, which is a solid foundation and a guarantee from the ancient times of continuous development of the Chinese civilization. Kеy words: Confucius, Confucianism, ideology